2015
DOI: 10.1038/pr.2015.273
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in late preterm infants according to percentile at birth

Abstract: Background:The data on body composition of late preterm infants, evaluated according to percentile at birth, are scarce. The study aimed to investigate body composition of late preterm infants, according to percentile at birth, and to compare their body composition with that of term newborns. Methods: A total of 122 (99 appropriate and 23 small for gestational age (SGA)) late preterm infants underwent growth and body composition assessment using an air displacement plethysmography system on the fifth day of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…On the other hand, it is acknowledged that nutrition accounts only for 50% of the variance in early postnatal growth [21] and, as a result, other factors could contribute to the increased fat mass content at term that has been found also by other authors [3,4,5,6]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it is acknowledged that nutrition accounts only for 50% of the variance in early postnatal growth [21] and, as a result, other factors could contribute to the increased fat mass content at term that has been found also by other authors [3,4,5,6]. …”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the institutional review board of the Fondazione Istituto di Ricovero e Cura a Carattere Scientifico Cà Granda Ospedale Maggiore Policlinico, and written informed consent from the infants' parents was obtained. All consecutive newborns admitted to the authors' institution between 2014 and 2015, including those previously enrolled into a previous study [4], were screened for eligibility.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Late preterm infants show increased mortality and morbidity compared with full-term newborn infants [2]. It has been reported that the first months of the postnatal life of late preterm infants are characterized by rapid postnatal catch-up growth, and as a result, at term-corrected age, late preterm infants achieve a weight either comparable to or higher than full-term newborns [3,4]. Evidence indicates that early body composition development in these infants is accompanied by a major deposition of fat mass so that, at term-corrected age, increased adiposity irrespective of the percentile at birth has been found.…”
Section: Introductionmentioning
confidence: 99%